2018
DOI: 10.1007/s00438-018-1422-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation analysis in jejunum of Sus scrofa with intrauterine growth restriction

Abstract: Intrauterine growth restriction (IUGR) may elicit a series of postnatal body developmental and metabolic diseases due to their impaired growth and development in the mammalian embryo/fetus during pregnancy. In the present study, we hypothesized that IUGR may lead to abnormally regulated DNA methylation in the intestine, causing intestinal dysfunctions. We applied reduced representation bisulfite sequencing (RRBS) technology to study the jejunum tissues from four newborn IUGR piglets and their normal body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Previous studies showed that the intestinal permeability of LBW piglets was nearly twice as high as that of normal piglets, suggesting impaired intestinal epithelial barrier function (23). A subsequent study found that LBW-induced changes in methylation in the intestine were mainly involved in biological processes, such as cell apoptosis and cell differentiation, suggesting that LBW piglets have a higher incidence of intestinal dysfunction (24). The adverse effects of LBW on fetuses and newborns may persist throughout the life cycle (25,26).…”
mentioning
confidence: 99%
“…Previous studies showed that the intestinal permeability of LBW piglets was nearly twice as high as that of normal piglets, suggesting impaired intestinal epithelial barrier function (23). A subsequent study found that LBW-induced changes in methylation in the intestine were mainly involved in biological processes, such as cell apoptosis and cell differentiation, suggesting that LBW piglets have a higher incidence of intestinal dysfunction (24). The adverse effects of LBW on fetuses and newborns may persist throughout the life cycle (25,26).…”
mentioning
confidence: 99%
“…However, our results demonstrate a significantly less dense microvasculature in LBW when compared to NBW piglets, the latter showing 85% more endothelial mass per unit of intestinal tissue than LBW. Due to the implications of microcirculation on intestinal health, nutrient transportation and intestinal permeability (Cummins & Crean, 2017), we could speculate that its deficiency contributes to the lesser growth and feed efficiency, to the increased morbidity and to incidence of intestinal underdevelopment, observed in LBW piglets (Dong et al, 2014;Hu et al, 2018;Mickiewicz et al, 2012;Wang et al, 2015;Wu, Bazer, Wallace, & Spencer, 2006). However, it is noteworthy that the vWF-positive area is similar in both birthweight categories at birth and becomes larger in 3-day old NBW piglets.…”
Section: Vwf and Enos Immunoreactivitymentioning
confidence: 97%
“…Notably, most genes that are differentially expressed at the transcriptional level between the suckling and weaning periods stabilize expression levels after weaning, suggesting that early life transitional states can influence gene expression in adult intestines (46) . Intra uterine growth restriction can also cause DNA methylation abnormalities (52) , which could contribute to the gastrointestinal dysfunctions presented by infants with very low birth weight.…”
Section: Dna Methylation and Intestinal Development And Proliferationmentioning
confidence: 99%